Comparative analysis of the whole transcriptome landscapes of muscle and adipose tissue in Qinchuan beef cattle - Ju Qiu; Zheng Ma; Zhipeng Hong; Xu Yin; Yun Chen; Hafiz Qadeer Ahmed; Linsen Zan; Anning Li (BMC Genomics)
Abstract Background Muscle and adipose tissue are the most critical indicators of beef quality, and their development and function are regulated by noncoding RNAs (ncRNAs). However, the differential regulatory mechanisms of ncRNAs in muscle and adipose tissue remain unclear. Results In this study, 2,343 differentially expressed mRNAs (DEMs), 235 differentially expressed lncRNAs (DELs), 95 differentially expressed circRNAs (DECs) and 54 differentially expressed miRNAs (DEmiRs) were identified in longissimus dorsi muscle (LD), subcutaneous fat (SF) and perirenal fat (VF) in Qinchuan beef cattle. The results of functional enrichment analysis showed that DEMs, DELs, DECs and DEmiRs were enriched in biological processes related to development and function of muscle and fat deposition, including skeletal muscle contraction, muscle organ development, PPAR signaling pathway, fatty acid metabolism and MAPK signaling pathway. Based on the competing endogenous RNA (ceRNA) regulatory mechanism, we constructed a lncRNA/circRNA-miRNA-mRNA network consisting of 6 circRNAs, 5 lncRNAs, 6 miRNAs and 27 mRNAs. Among them, 55 ceRNA axes were involved, including circRNA12990 - bta-miR-133a_L-1R + 1 - MYO6/ZEB2, circRNA2893/MSTRG.28538.1/MSTRG.11613.4 - pma-miR-145-5p_R + 2 - EYA4 and MSTRG.26982.1 - bta-let-7e_R + 1 - RBM40. Conclusions This study identified a group of differentially expressed mRNAs, lncRNAs, circRNAs and miRNAs between muscle and adipose tissue and constructed a potential ceRNA regulatory network, which may serve as a foundation for studying the differential regulatory roles of ncRNAs in the development and function of muscle and adipose tissue.